Thermodynamics of Hydrogen in thin films and mathematical calculations - Munkhsaikhan G, (Scientific transaction of the National University of Mongolia. Physics, 2022)
Abstract: The behavior of Mg/Pd and Mg/Cr thin films, exposed to a hydrogen pressure, was investigated. Two experimental methods for determining the thermodynamics of hydrogen in thin films have been presented in this paper. The first method based on the dependency of the resistance variation rate of the sample on hydrogen pressure and used for determining plateau pressure. The second approach is relying on the on hydrogen uptake during the hydrogen loading process. The bulk data for comparison have been calculated using mathematical calculations.